False Institutional Affiliations and Gaming University Metrics - Bachelet, Vivienne C. (International Higher Education, 2021)
Publications are used by ranking houses to build their indicators on university quality. Many universities worldwide pay their academics and scientists cash rewards for publishing in high-impact or indexed journals, as a way of increasing their productivity. However, universities may be using other mechanisms to increase the numbers of publications that are credited to their account, gaming the metrics used to rank universities.